2012
DOI: 10.1177/0961203312454343
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating systemic lupus erythematosus patients for lung involvement

Abstract: Respiratory symptoms, abnormal lung function, and SLS are common in SLE. Clinicians should consider evaluation for SLS among symptomatic patients with long-standing disease and a history of pleuritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 44 publications
5
38
1
Order By: Relevance
“…Moreover, our results suggested that the presence of anti-RNP at diagnosis is associated a greater incidence of arthritis and rash and may significantly promote the development of arthritis, rash, and mucosal ulcers, thus contributing to SLE flare according to the SLEDAI-2K definition, a finding that was consistent with the results of a previous study [9]. On the other hand, in contrast to previously reported results, the incidence of diffuse interstitial lung disease and pulmonary arterial hypertension did not differ according to the presence of anti-RNP [10]. However, a 1-year follow-up period might not be sufficient to identify histological alterations that lead to clinical symptoms.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, our results suggested that the presence of anti-RNP at diagnosis is associated a greater incidence of arthritis and rash and may significantly promote the development of arthritis, rash, and mucosal ulcers, thus contributing to SLE flare according to the SLEDAI-2K definition, a finding that was consistent with the results of a previous study [9]. On the other hand, in contrast to previously reported results, the incidence of diffuse interstitial lung disease and pulmonary arterial hypertension did not differ according to the presence of anti-RNP [10]. However, a 1-year follow-up period might not be sufficient to identify histological alterations that lead to clinical symptoms.…”
Section: Discussionsupporting
confidence: 88%
“…According to previous studies, the presence of anti-RNP was thought to correlate with typical symptoms of MCTD, Raynaud's phenomenon, and mild renal diseases in SLE patients [6,8]. In addition, SLE patients with anti-RNP were found to more frequently manifest malar rash, arthritis, and serositis [9], as well as a much higher prevalence of pulmonary hypertension or lung fibrosis higher SLE Disease Activity Index (SLEDAI) scores, compared to SLE patients without anti-RNP [10,11]. However, to our knowledge, few studies have clarified the association between anti-RNP and changes in SLE activity, especially SLE flares, during a considerable follow-up period.…”
Section: Introductionmentioning
confidence: 99%
“…Direct autoantibodyand immune complex-mediated tissue damage is related to clinical expression [73,74] . Respiratory manifestations occur commonly in SLE, mainly infective pneumonias, pleural disease and pulmonary thromboembolism [75,76] (see online suppl. table 2).…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…table 2). 'Acute lupus pneumonitis' is a term commonly used by clinicians to define the 'lupus' patient who presents with fever and pulmonary infiltrates [76,77] . This term refers to nothing specific (probably a misnomer) since the differential diagnosis includes several acute respiratory conditions that occur in SLE such as infective pneumonia, pulmonary infarcts, DAH, COP or others, and a special effort should be made to assure diagnosis and target treatment [78,79] ( fig.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Aside from these associations, no study has recorded the predicted accuracy of these correlations and, as a result, chest radiography has been the suggested method to diagnose lung injury (Levitt et al, 2013). Since evidence of lung damage is reported in both of these autoimmune syndromes and indicated to be the leading cause of mortalities in MCTD patients (Prakash, 1992;Pehlivan and Inanc, 2010;Allen et al, 2012), the U1Ap lung model should be considered as a new serological predictive factor for lung disease with the sensitivity and specificity of 81% and 77%, respectively, in patients with either SLE or MCTD ( Figure 5). …”
Section: Discussionmentioning
confidence: 99%